Translingual and transnational graduate education in rhetoric and composition - Bou Ayash, Nancy, editor; Kilfoil, Carrie Byars, editor; Utah State University Press, publisher (Colorado State University. Libraries, 2023)
This book systematically investigates the implications of composition studies' changing terminological and ideological landscape around language and nation for the education and professionalization of future writing teachers and specialists. Incorporating these theories into graduate pedagogy and curricular structures in composition is necessary to shape professional practices in the field long term.--Provided by publisher.
Doing translingualism through panoramic ethos: three transnational graduate students' pathways across multiliteracies and implications for program practices / Corina Lerma, Moisés Garc̕ía Renter̕a, Patricia Flores, Kate Mangelsdorf, and Lucía Durá -- (En)countering monolingual, fast-capitalist comp/rhet: a transnational sensemaking of graduate education / Emily Yuko Cousins, Joe Franklin, and Alex Way -- The postmonolingual condition and the rhetoric and composition phd: norming language difference in a doctoral program / Carrie Byars Kilfoil -- Transforming graduate education in rhetoric and composition: toward a transnational and translingual revaluation / Bruce Horner -- Translation and translingual competence in graduate training / Nancy Bou Ayash -- Comparative rhetoric and the translingual future of mentorship / Michelle Zaleski and Xiaoye You -- The role of graduate education in building writing teachers' knowledge of language / Madelyn Pawlowski and Christine M. Tardy -- A translingual approach to tutoring international graduate students / Aimee Jones -- Shifting the paradigm of translingual and transnational graduate education / Amy J. Wan -- Translingualism and transnationalism as decolonial recovery / Anselma Widha Prihandita -- Distributing the labor of translation in the context of graduate education in writing studies / Joe Wilson -- Translingual and transnational graduate education for the local public good / Brice Nordquist.
Keywords: English language -- Rhetoric -- Study and teaching (Graduate); Academic writing -- Study and teaching (Graduate); Multilingual education; Multilingualism -- Study and teaching (Graduate); Transnational education; Transnationalism -- Study and teaching (Graduate)